Designing and implementing a COPD discharge care bundle. Issue 1 (16th August 2011) - Hopkinson, Nicholas S; Englebretsen, Catherine; Cooley, Nicholas; Kennie, Kevin; Lim, Mun; Woodcock, Thomas; Laverty, Anthony A; Wilson, Sandra; Elkin, Sarah L; Caneja, Cielito; Falzon, Christine; Burgess, Helen; et al.
Abstract : National surveys have revealed significant differences in patient outcomes following admission to hospital with acute exacerbation of COPD which are likely to be due to variations in care. We developed a care bundle, comprising a short list of evidence-based practices to be implemented prior to discharge for all patients admitted with this condition, based on a review of national guidelines and other relevant literature, expert opinion and patient consultation. Implementation was then piloted using action research methodologies with patient input. Actively involving staff was vital to ensure that the changes introduced were understood and the process followed. Implementation of a care bundle has the potential to produce a dramatic improvement in compliance with optimum health care practice.